UPAYA MENINGKATKAN HASIL BELAJAR PPKn MELALUI MODEL PEMBELAJARAN STUDI KASUS BERBASIS E-LEARNING PADA MATERI KASUS-KASUS PELANGGARAN HAK DAN PENGINGKARAN KEWAJIBAN WARGA NEGARA DI KELAS XII RPL B SMK NEGERI 1 PAJANGAN - Sugiyarti Sugiyarti (INCARE, International Journal of Educational Resources, 2021)
The purpose of this study is to improve students' learning outcomes in PPKn subjects through an E-Learning-based case study learning model. The research was conducted at SMK Negeri 1 Display with research subjects are students of class X II RPL B. This research is a class action research conducted through two cycles. Each cycle consists of four stages of action, namely planning, implementation, observation and reflection. Data collection uses student observation sheet instruments to determine the improvement of the affective aspects of students and instruments of student learning outcomes to determine the improvement of cognitive aspects. Teacher observation sheets are used to determine the teacher's ability to apply E-Learning-based case study learning models. Student questionnaires are used to obtain data on students' responses to E-Learning-based case study learning methods. Data analysis using qualitative descriptive. The criteria for success set is the value of student learning outcomes at least 75 with a completion of the class of 81%. The results of the study are known that the application of E-Learning-based case study learning model can improve students' learning outcomes. Before applying the E-Learning-based case study learning model only 58.33% or 14 students managed to achieve completion. After applying the E-Learning-based case study learning model increased to 70.83 % or 17 students in cycle I and increased again to 83.33 % or 20 students in cycle II. Thus, it can be concluded that the application of E-Learning-based case study learning model succeeds in improving student learning outcomes.